Multimodal Hybrid Piezoelectric-Electromagnetic Insole Energy Harvester Using PVDF Generators - Muhammad Iqbal (114924) (2020)
Harvesting biomechanical energy is a viable solution to sustainably powering wearable electronics for continuous health monitoring, remote sensing, and motion tracking. A hybrid insole energy harvester (HIEH), capable of harvesting energy from low-frequency walking step motion, to supply power to wearable sensors, has been reported in this paper. The multimodal and multi-degrees-of-freedom low frequency walking energy harvester has a lightweight of 33.2 g and occupies a small volume of 44.1 cm3. Experimentally, the HIEH exhibits six resonant frequencies, corresponding to the resonances of the intermediate square spiral planar spring at 9.7, 41 Hz, 50 Hz, and 55 Hz, the Polyvinylidene fluoride (PVDF) beam-I at 16.5 Hz and PVDF beam-II at 25 Hz. The upper and lower electromagnetic (EM) generators are capable of delivering peak powers of 58 µW and 51 µW under 0.6 g, by EM induction at 9.7 Hz, across optimum load resistances of 13.5 Ω and 16.5 Ω, respectively. Moreover, PVDF-I and PVDF-II generate root mean square (RMS) voltages of 3.34 V and 3.83 V across 9 MΩ load resistance, under 0.6 g base acceleration. As compared to individual harvesting units, the hybrid harvester performed much better, generated about 7 V open-circuit voltage and charged a 100 µF capacitor up to 2.9 V using a hand movement for about eight minutes, which is 30% more voltage than the standalone piezoelectric unit in the same amount of time. The designed HIEH can be a potential mobile source to sustainably power wearable electronics and wireless body sensors. Other Information Published in: Electronics License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/electronics9040635